L’anniversaire des “Annales”. The Year 2014 as the Time of French Anniversaries of Marc Bloch, Philipp Aries and Jacques le Goff - Głowacka-Sobiech, Edyta (Biuletyn Historii Wychowania, 2018)
Article presents achievements of three French historians: Marc Bloch (1886–1944), Philipp Ariès (1914–1984) and Jacques le Goff (1924–2014). They were founders and leaders of Annales school in historiography. Marc Bloch was fascinated by the history of the Middle Ages, especially the history of the French countryside and feudalism, as well as the social history of medieval France. Philippe Ariès was also passionate about the history of the Middle Ages, but unlike Bloch, he was more interested in everyday matters such as death and childhood. Thanks to his work on childhood, he made a breakthrough in historiography dealing with such a delicate and elusive topic, while making very radical judgments about the issue. Jacques le Goff was known in the Annalist community as the creator of nouvelle histoire, i.e. historical anthropology and the history of mentality. Thanks to historians like J. Le Goff, history seemed more interesting and “fresh”, even, and above all, the history of the Middle Ages.